The Mediating Roles of Resilience and Flow in Linking Basic Psychological Needs to Tertiary EFL Learners’ Engagement in the Informal Digital Learning of English: A Mixed-Methods Study - Yang Gao; Xiaochen Wang; Barry Lee Reynolds (Behavioral Sciences)
Resilience and flow are crucial in language education, yet most research focuses on formal learning environments, with limited studies on their impact in informal settings. This study explores the relationship between basic psychological needs and engagement in the context of informal digital English learning (IDLE). Using a mixed-methods design, data were collected from 512 Chinese EFL learners. Structural equation modeling and NVivo analysis were applied to quantitative and qualitative data, respectively. The findings reveal that resilience fully mediates the relationship between basic psychological needs and engagement, serving as an adaptability enhancer, persistence promoter, stress buffer, self-efficacy builder, and emotional regulation facilitator. Conversely, flow partially mediates this relationship, though perceived competence does not significantly predict flow in this context. Building on this, flow contributes as an intrinsic motivation driver, positive cycle creator, external pressure mitigator, and efficiency enhancer. This research underscores the important role of resilience and flow in IDLE among Chinese university EFL students. By highlighting these mediating roles, the study provides valuable insights for enhancing the effectiveness of IDLE experiences, contributing to the broader discourse on language education in the digital age.